Epiphytic diatoms associated with red mangrove (Rhizophora mangle) prop roots in Bahía Magdalena, Baja California Sur, Mexico - Siqueiros Beltrones, D. A.; López Fuerte, F. O. (Revista de Biología Tropical, 2006)
The first floristic inventory of benthic diatoms is provided for the Bahía Magdalena-Bahía Almejas lagoon system. Samplings were carried out during November of 1999. The oxydized samples were mounted permanently. Eighty six diatom taxa were identified, out of which 59 are new records for the Bahía Magdalena area, and 12 taxa are new for the Baja California peninsula. Taxa recorded previously as rare in other substrata are common or abundant on the epiphytic macroalgae of mangrove prop roots. Other species are mainly epipelic forms, while 24 are commonly found as tychoplankton in the area. Certain taxa appear to be characteristic of mangrove systems in general.